Serum Levels of miR-143 Predict Survival in Critically Ill Patients. (23rd October 2019) - Roderburg, Christoph; Koch, Alexander; Benz, Fabian; Vucur, Mihael; Spehlmann, Martina; Loosen, Sven H.; Luedde, Mark; Rehse, Sebastian; Lurje, Georg; Trautwein, Christian; Tacke, Frank; Luedde, Tom
Abstract : Background and Aims . Recent data suggested a potential role of miR-143 as a biomarker for systemic inflammation and infection. However, its role in critical illness and sepsis is only poorly understood. Methods . We determined circulating levels of miR-143 in 218 critically ill patients, of which 135 fulfilled sepsis criteria, and compared them to 76 healthy controls. Results were correlated with clinical records. Results . In the total cohort of critically ill patients from a medical intensive care unit (ICU), miR-143 serum levels tended to be lower compared to healthy control samples, but this difference did not reach statistical significance. In ICU patients, serum levels of miR-143 were independent of disease etiology, including the presence of sepsis, or severity of disease. Importantly, low miR-143 serum levels were associated with an unfavorable short- and long-term prognosis in ICU patients. Our study identified different optimal cut-off values at which low miR-143 serum levels predicted mortality with a high diagnostic accuracy. In line with this, concentrations of circulating miR-143 correlated with markers of organ failure such as creatinine, bilirubin, or lactate in our cohort of critically ill patients. Conclusion . Low miR-143 serum levels are indicative for an unfavorable short- and long-term prognosis in critically ill patients admitted to a medical ICU. Our data suggest a previously unrecognized role for miR-143 measurements as a novel prognostic marker in critically ill patients.